A contribution to the contractual analysis of public-private partnerships - Sarah Jamil; Bernhard Neumärker (University of Freiburg, Institute for Economic Research, Department of Economic Policy and Constitutional Economic Theory, 2010)
The advantages and the epistemological value of constitutional economics make them a designated research background for a constitutional examination of PPP. The constitutional approach provides an adequate framework that allows clarifying how the process of PPPs may be improved by constitutional restrictions. The relationship among state and the citizens is a principal-agent relationship, whereas builder and operator have an informal advantage in the post constitutional stage. Aim is to design a constitution that makes the state follow a practice for PPP that is in his own interest, as well as in the interest of the citizenry. A normative model of PPP is melted with a formal framework that will be used as a basis for an application of a constitutional stage. It will be shown how a pre-play phase, reciprocal behaviour and a constitutional stage can affect the achievement of first-best outcomes.
Keywords: 330